Iraqi EFL Preparatory School Teachers’ Perception Regarding Teacher Competencies of Self-Directed Learning - Hussein, Shahad Dheyaa; Al-Bakri, Shaimaa Abdulbaqi (Al-Adab Journal, 2022)
Although self-directed learning is regarded as a skill of the 21st century and as a motivation for students in educational practice and theory, self-directed learning is considered to be challenging for most teachers to be integrated into their practice. Meanwhile, teachers are required to consider each student as a unique and distinguished individual. This means that students in every classroom have diverse talents and abilities to learn differently and are able to develop at a different level. Thus, Iraqi EFL preparatory school teachers must be informed of all ideas, concepts, and methods relating to English language learning. The current study aims at finding out how Iraqi EFL preparatory school teachers perceive teacher competencies of self-directed learning and if there are any significant differences between them due to their gender and years of experience. The participants are (300) EFL preparatory school teachers from Baghdad Governorate / the General Directorate of Education - Al-Karkh 3rd. An online closed questionnaire has been submitted to the participants using Google forms. The results reveal that Iraqi EFL preparatory school teachers have positively perceived teacher competencies of self-directed learning, and that there are significant differences between them according to their years of experience.